Cardiovascular complications of COVID-19 in hospitalized patients, systematic review of the literature - Mejia-Zambrano, Henry (2021)
IBackground: The COVID-19 disease caused by the virus, SARS-CoV-2, began in the Wuhan region of the People's Republic of China at the end of 2019, causing complications and mortality in hospitalized patients. Objective: To systematically review the literature on the cardiovascular complications of COVID-19 in hospitalized patients. Methods: Observational studies, studies on cardiovascular complications in hospitalized patients for COVID-19, studies with available texts and, studies in English and Spanish were included. A narrative synthesis of the collected data was carried out, without a formal statistical analysis. In addition to qualitative analysis of the main reported pathologies and clinical manifestations, the study quality tool of the United States National Institutes of Health was used. Results: In this study it was observed that 50.6% of the patients infected by SARS-CoV-2 suffered some cardiovascular comorbidity (43.5% arterial hypertension (HTA) and 19.8% diabetes mellitus). The complications of COVID-19 in infected patients were: (44.1%) venous thromboembolism, (32%) acute myocardial infarction (AMI), (19.2%) myocarditis, (16.3%) arrhythmia and (11.2%) cerebrovascular disease. Conclusion: The main cardiovascular effects in patients infected by SARS-COV-2 were myocarditis, acute myocardial infarction (AMI), venous thromboembolism, cerebrovascular disease (CVD).